Early readmission in a high complexity public hospital in cardiology - Hermínia Ricci; Mara Nogueira de Araújo; Sérgio Henrique Simonetti (Rev Rene)
Objective: to evaluate the early readmission of patients in a high complexity public hospital in cardiology. Methods: this is a descriptive, documental and retrospective study, carried out in a public hospital. Results: in 2012, 729 of the 9,218 hospitalized patients were readmitted, 47.9% of them were readmitted within 30 days after discharge, 61% were men, with a mean age of 57 years old, with the main medical diagnosis of heart disease (heart failure, treatment of acute coronary syndrome, among others) on admission (44.7%) and readmission (45.8%). Most were readmitted for the same medical reason that led to their first hospitalization. Conclusion: considering the profile of the population admitted and readmitted to the institution, it is believed that the rate of readmission is mainly due to the profile of the patients, considering the high prevalence of non-communicable chronic diseases, and coronary artery disease considered unapproachable for percutaneous or surgical when hospitalized.